Analisis Nilai-Nilai Pendidikan Islam dalam Novel Bumi Karya Tere Liye - Muhammad Aqmal Ramadhan Nugraha; Ayi Sobarna; Heru Pratikno (UNISBA Press, 2024)
Abstract. This thesis examines the Islamic educational values contained in the novel Bumi by Tere Liye and the relevance of these values to Islamic Education (PAI) learning. This research uses a qualitative approach with content analysis method to explore and analyze the implicit values in the novel. The analysis results show that the novel Bumi contains Islamic educational values such as simplicity, honesty, independence, gratitude, and patience. The value of simplicity is reflected through the character Raib, who is not obsessed with popularity and enjoys simple things in life. Honesty is evident when Raib admits his forgetfulness of bringing his homework book, even though he has to face the consequences. Independence is embodied through Mama Raib, who is able to solve technical problems without the help of others. Raib also shows gratitude for every moment, even when rain pours down on the school. The virtue of patience is demonstrated by Raib as he is able to restrain himself and avoid conflicts with his friends.The relevance of these values to PAI learning lies in their potential to shape students' characters with noble morals. This thesis highlights the importance of literature, particularly novels, as a medium for Islamic Education learning that can provide concrete and inspirational examples for students. By exemplifying characters and stories in novels, PAI learning can become more engaging and relevant to daily life. This thesis contributes to the development of Islamic education in Indonesia by showing that novels can be an effective educational medium in shaping students with noble morals who are beneficial to society. Abstrak. Skripsi ini mengkaji nilai-nilai pendidikan Islam yang terkandung dalam novel Bumi karya Tere Liye dan relevansi nilai-nilai tersebut terhadap pembelajaran Pendidikan Agama Islam (PAI). Penelitian ini menggunakan pendekatan kualitatif dengan metode analisis isi untuk menggali dan menganalisis nilai-nilai yang tersirat dalam novel. Hasil analisis menunjukkan bahwa novel Bumi mengandung nilai-nilai pendidikan Islam seperti kesederhanaan, kejujuran, kemandirian, syukur, dan sabar. Nilai kesederhanaan tercermin melalui karakter Raib yang tidak terobsesi dengan popularitas dan menikmati hal-hal sederhana dalam hidup. Kejujuran terlihat ketika Raib mengakui kelupaannya membawa buku PR, meskipun harus menghadapi konsekuensi. Kemandirian diwujudkan melalui Mama Raib yang mampu mengatasi masalah teknis tanpa bantuan orang lain. Raib juga menunjukkan rasa syukur atas setiap momen, bahkan saat hujan mengguyur sekolah. Sikap sabar ditunjukkan oleh Raib saat dia mampu menahan diri dan menghindari konflik dengan teman-temannya. Relevansi nilai-nilai ini terhadap pembelajaran PAI terletak pada potensi mereka untuk membentuk karakter siswa yang berakhlak mulia. Skripsi ini menyoroti pentingnya sastra, khususnya novel, sebagai media pembelajaran PAI yang dapat memberikan contoh konkret dan inspiratif bagi siswa. Dengan mencontoh karakter dan kisah dalam novel, pembelajaran PAI dapat menjadi lebih menarik dan relevan dengan kehidupan sehari-hari. Skripsi ini memberikan kontribusi terhadap pengembangan pendidikan Islam di Indonesia dengan menunjukkan bahwa novel dapat menjadi media edukatif yang efektif dalam membentuk karakter siswa yang berakhlak mulia dan berdaya guna bagi masyarakat.